The Putative Methyltransferase TlLAE1 Is Involved in the Regulation of Peptaibols Production in the Biocontrol Fungus Trichoderma longibrachiatum SMF2 - Shi, Jin-Chao; Shi, Wei-Ling; Zhou, Yan-Rong; Chen, Xiu-Lan; Zhang, Yu-Zhong; Zhang, Xia; Zhang, Wei-Xin; Song, Xiao-Yan (Frontiers in Microbiology, 2020)
The biocontrol fungus Trichoderma longibrachiatum SMF2 secretes a large quantity of peptaibols that have been shown to have a range of biological activities and therefore great application values. However, the mechanism of the regulatory expression of peptaibols is still unclear. The putative methyltransferase LaeA/LAE1 is a global regulator involved in the biosynthesis of some secondary metabolites in filamentous fungi. In this study, we demonstrated that the orthologue of LaeA/LAE1 in the biocontrol fungus T. longibrachiatum SMF2, TlLAE1, plays an important role in the regulation of peptaibols production. Deletion of Tllae1 resulted in a slight negative impact on mycelial growth, and a significant defect in conidial production. Deletion of Tllae1 also compromised the production of peptaibols to a large degree. Further analyses indicated that this defect occurred at the transcriptional level of the two synthetases-encoding genes, tlx1 and tlx2, which are responsible for peptaibols production. By contrast, constitutive expression of Tllae1 in T. longibrachiatum SMF2 led to two-fold increased peptaibols production, suggesting that this is a strategy to improve peptaibols production in Trichoderma fungi. These results demonstrate the important role of LAE1 in the regulation of peptaibols production in T. longibrachiatum SMF2.